2015
DOI: 10.14429/djlit.35.5.8788
|View full text |Cite
|
Sign up to set email alerts
|

Webometric analysis of Library Websites of Higher Educational Institutes (HEIs) of India: A study

Abstract: Library websites plays an important role in dissemination of information of the institution and library resources. It acts as a trustworthy mirror of the institute. To evaluate the library website performance webometric tools and indicators are required. The present study calculated web impact factor (WIF) and R-WIF (Revised WIF) of top ten library websites of HEIs (Higher Educational Institutes) of India and further correlated both the formulas with Spearman's Rank Correlation. It was found that WIF and R-WIF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Furthermore, in this study, they implemented an automated ranking and recommendation system for Lebanon university websites. Chakravarty and Wasan (2015) calculated the WIF and RWIF of top 10 library websites of higher education institutes in India by desiring Google search engine and correlated these two formulas. Their results shown that the positive and strong relationship between WIF and RWIF were very less difference between the two ranking methods.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in this study, they implemented an automated ranking and recommendation system for Lebanon university websites. Chakravarty and Wasan (2015) calculated the WIF and RWIF of top 10 library websites of higher education institutes in India by desiring Google search engine and correlated these two formulas. Their results shown that the positive and strong relationship between WIF and RWIF were very less difference between the two ranking methods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, it should be enormous, cover more hyperlinks with advanced search facilities to count links possessed by the websites (Chakravarty & Wasan, 2015). The WIF studies conducted by Ingwersen (1998), Thomas and Willett (2000), Smith and Thelwall (2002) Jalal, Biswas and Mukhopadhyay (2010) and Parrish (2016) mentioned that AltaVista was once the most popular search engine, and for a while ranked closely behind Google and Yahoo but from 2004, AltaVista was owned by Yahoo and AltaVista's home page was redirected to Yahoo's main page with powered from the Yahoo search index.…”
Section: Selection Of Search Enginementioning
confidence: 99%